PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE ERHA DI KOTA BATAM - William wilson xiee; Inda Sukanti (SCIENTIA JOURNAL, 2025)
This research analyzes the impact of brand ambassadors, promotions, and brand image on purchasing decisions for Skintific Skincare products in Batam City. This study applies to a quantitative research approach. This study involved 100 respondents who had purchased and used Skintific Skincare products in Sagulung District, Batam City. The approach used to collect data was by using a questionnaire. Data processing was carried out using the SPSS version 26 program. Based on the analysis and data that have been obtained, this study shows that brand ambassadors have a positive and significant influence on purchasing decisions for Skintific Skincare products in Batam City. In addition, promotions that are carried out positively and significantly have an impact on purchasing decisions for Skintific Skincare products in Batam City. The brand image variable positively and significantly impacts purchasing decisions for Skintific Skincare products in Batam City. Simultaneously, brand ambassadors, promotions and brand image positively and significantly influence purchasing decisions for Skintific Skincare products in Batam City